A comparative analysis on the uniformity enhancement methods of solar thermal drying - Husham Abdulmalek, S. (Elsevier Ltd, 2018)
The uniformity of solar drying process and the quality of the product are inter-related parameters. Drying uniformity is influenced by the significant process air properties which are temperature, humidity and velocity. Accordingly, solar drying uniformity may be improved by integration with dehumidification system and/or optimizing the dryer design. These concepts were reviewed extensively in this paper by brush up the solar thermal hybrid dryers, the performance of solar assisted desiccant systems for dehumidification of drying air, the effect of geometrical parameters on drying performance, and the drying performance of different products. In the context of desiccant systems, the performance of drying is influenced by desiccant material, dehumidifier design and regeneration technique used. While, the issue of solar dryer design is related to drying chamber geometrical parameters, considering multiple drying chambers, and modeling and optimization of dryer design. Coming out with this comprehensive review may motivate to enhance the quality of product and drying performance in terms of cost and time. Â© 2018 Elsevier Ltd